2008
DOI: 10.1177/1077801208320365
|View full text |Cite
|
Sign up to set email alerts
|

Gender Violence Among Teenagers

Abstract: This Spanish-based study found that some adolescents link attractiveness with violence. Previous research showed that a socialization process within teenagers' contexts promotes this association. The results suggest that this link is one of the possible causes of the high rates of gender violence among youth. Debates regarding this research already have had political repercussions. Although the 2004 Spanish Act Against Gender Violence--the first of its kind in Europe--acknowledged violence with romantic partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 25 publications
(18 reference statements)
6
32
0
7
Order By: Relevance
“…This last effect is an issue which has been widely explored by previous research (Bukowski et al, 2000) making visible how heterosexual girls who desire this typology of guys are more likely to have abusive dating or abusive marital relations. In fact, research has also demonstrated that the existence of a socialization process that links dominance and attractiveness is an important explanatory factor of IPV in teenagers (Valls et al, 2008). However, present investigation goes beyond these analyses and illustrates how girls' choices in their affective and sexual relationships are conditioned by the interactions and the language used within the family environment.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…This last effect is an issue which has been widely explored by previous research (Bukowski et al, 2000) making visible how heterosexual girls who desire this typology of guys are more likely to have abusive dating or abusive marital relations. In fact, research has also demonstrated that the existence of a socialization process that links dominance and attractiveness is an important explanatory factor of IPV in teenagers (Valls et al, 2008). However, present investigation goes beyond these analyses and illustrates how girls' choices in their affective and sexual relationships are conditioned by the interactions and the language used within the family environment.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, every-day interaction spaces, like the ones established in family, contribute to foster or reject certain models of attractiveness, so these spaces become very important at early ages. Recent studies on this line illustrate an alarming problem concerning the existence of models of attractiveness which are connected to violent behaviors, this means that young people and adolescents are being socialized on attraction toward violence and this can drive them to toxic relationships marked by IPV (Valls et al, 2008). Valls et al (2008) confirmed that issue and they discovered that this link between aggressiveness and attractiveness is due a chauvinist socialization process which promotes desire toward masculine models that are dominant and violent.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…It is important to highlight the study by Valls, Puigvert and Duque (2008), which demonstrates that certain adolescents have been socialized into forming a type of relationship that results from this association. These authors performed their study in the Spanish context while drawing on previous research that reports a socialization process 188 Puigvert -Female Univesity Students Respond to Gender Violence within adolescent contexts that enhances this link.…”
Section: International and Multidisciplinary Journal Of Socialmentioning
confidence: 99%